Parametric system identification of thermoelectric cooler for single photon avalanche diode application - Samsuddin, Nurul Izzati; Ahmad, Salmiah; Hasbullah, Nurul Fadzlin; Toha, Siti Fauziah (Maxwell Scientific Organization, 2012, 2013)
The purpose of this study is to model the thermoelectric coolers (TEC) by means of computational intelligence system identification. Thermoelectric coolers are widely used in cooling, maintaining and stabilizing the temperature of the Single photon avalanche diode (SPAD). SPAD is a temperature sensitive optoelectronic device, where even a slight variation in temperature can cause unstable performance in quantum efficiency, responsitivity and dark counts. However, it is not a simple task to derive a mathematical model for TEC since it varies with the operating condition. In this paper, particle swarm optimization (PSO) was used in order to identify the mathematical model of the multistage TEC (1639733 from Element 14), which encapsulates dynamics of the SPAD, heatsink and components of the cooling heat exchanger. The model was validated by correlation tests, percentage accuracy and also by comparing its time and frequency responses against that of the TEC. It was found that the obtained model has a good representation of the actual system.